2010
DOI: 10.1111/j.1752-699x.2010.00217.x
|View full text |Cite
|
Sign up to set email alerts
|

Budesonide/formoterol maintenance and reliever therapy versus conventional best standard treatment in asthma in an attempted ‘real life’ setting

Abstract: Budesonide/formoterol maintenance and reliever therapy resulted in a better overall asthma control with a significant lower daily IGCS dose compared with CBST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 19 publications
0
13
1
2
Order By: Relevance
“…Budesonide/formoterol MRT was shown to provide effective asthma control and reduce the number and risk of severe exacerbations compared with other ICS/LABA combinations at similar or higher maintenance doses [ 3 , 4 , 5 , 6 ]. This novel regimen has also improved overall asthma control at a lower corticosteroid load compared with conventional best practice (including ICS/LABA plus SABA therapy at the physician’s discretion, as well as any additional controller medications at Global Initiative for Asthma [GINA] steps 3 and 4) [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Budesonide/formoterol MRT was shown to provide effective asthma control and reduce the number and risk of severe exacerbations compared with other ICS/LABA combinations at similar or higher maintenance doses [ 3 , 4 , 5 , 6 ]. This novel regimen has also improved overall asthma control at a lower corticosteroid load compared with conventional best practice (including ICS/LABA plus SABA therapy at the physician’s discretion, as well as any additional controller medications at Global Initiative for Asthma [GINA] steps 3 and 4) [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies also compared the SiT approach with conventional guideline-based best practice. [ 284 285 286 287 288 ] In these studies, though asthma control was better in the SiT group, number of exacerbations, lung function and symptoms were similar between the two arms. The dose of ICS used was however significantly lower with the SiT approach.…”
Section: E Management Of Stable Asthmamentioning
confidence: 85%
“…Symbicort SMART® therapy has been proven to be effective in improving lung function, asthma control and reducing asthma exacerbation at lower steroid load. [17][18][19] A post hoc pooled analysis 20 of results from 5 large clinical trials involving more than 12,000 patients and a meta-analysis 21 of 6 randomised controlled trials (RCTs) had also demonstrated that Symbicort SMART® therapy is highly effective in treating asthmatics requiring treatment adjustments across steps 2 to 4 in the GINA or Joint BTS/SIGN treatment guidelines, especially among patients whose asthma control is suboptimal because of under-treatment or whose asthma condition is more severe. Our study showed that 83% of Malaysian adult asthmatic patients treated with Symbicort® SMART in the primary care setting had good asthma control as defined by ACT scores ≥20.…”
Section: Discussionmentioning
confidence: 99%